TUNA FISH NUGGET PRODUCTION TRAINING TO INCREASE THE INCOME OF COASTAL COMMUNITIES IN BOTUTONUO VILLAGE - Usman Usman; Pratiwi Husain; Titi Umi Kalsum; Ikhlas Ul Aqmal; Hendra Pratama Danial (Journal of Entrepreneur, Business and Management, 2024)
This training program aims to optimize the potential of tuna fish resources in Botutonuo Village, Kabila Bone District, Bone Bolango Regency, through the production of tuna fish nuggets as a value-added, high-nutrition processed food product. Tuna fish in Botutonuo Village is abundantly available; however, it is predominantly sold in raw or fresh form and processed traditionally, resulting in limited economic value for the local community. Through this nugget production training, participants were equipped with practical skills in tuna nugget production, covering the stages of raw material preparation, batter mixing, steaming, cutting, coating, and frying. The resulting product demonstrated excellent quality characteristics: a bright golden-yellow color, a savory aroma characteristic of tuna and blended spices, a crispy outer texture with a soft interior, and a delicious taste. The product has good nutritional value due to its protein and Omega-3 content, and is suitable for consumption by all age groups. The program also identified challenges in maintaining batter consistency and product shape uniformity, which require further refinement in ingredient composition and production techniques. Tuna fish nugget production has great potential as a small-scale business that can increase community income and support the local coastal tourism sector, particularly in the coastal area of Botutonuo Village, Kabila Bone District, Bone Bolango Regency.Keywords: Tuna Fish Nugget, Fish Processing, Coastal Community, Botutonuo Village, Food Innovation.